A socio-ecological assessment of unemployment interventions in Cairo, Egypt - Fahmy, Hana Emad ElDin (AUC Knowledge Fountain, 2012)
An assessment of interventions working on solving the problem of unemployment in Cairo, Egypt was conducted in order to identify strengths, and to map out where interventions fell on a socio-ecological model. A one-day Appreciative Inquiry (AI) workshop was conducted for 16 participants who represented NGOs, social businesses, donors, training centers, recruitment agencies, technical institutes, educational institutions, and governmental organizations. Inductive content data analysis was used to analyze the themes that arose from the AI. Results show that 24% of the interventions work on multiple levels of the socio-ecological system. Strengths identified are having comprehensive interventions that tackle different aspects of unemployment and having access to funding, while participants envisioned a future where there washavingan overall, sharedvision for dealing with unemployment, strong networks and collaboration, better training programs and improved quality of programs through building capacity, and change in the societal attitudes that negatively influence the employment of individuals in Egypt. Building a coalition for interventions is recommended to enhance collaboration between them.